2009
DOI: 10.1124/jpet.109.160838
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol (Trans-3,5,4′-trihydroxystilbene) Induces Silent Mating Type Information Regulation-1 and Down-Regulates Nuclear Transcription Factor-κB Activation to Abrogate Dextran Sulfate Sodium-Induced Colitis

Abstract: Inflammatory bowel disease is a chronic, relapsing, and tissuedestructive disease. Resveratrol (3,4,5-trihydroxy-trans-stilbene), a naturally occurring polyphenol that exhibits beneficial pleiotropic health effects, is recognized as one of the most promising natural molecules in the prevention and treatment of chronic inflammatory disease and autoimmune disorders. In the present study, we investigated the effect of resveratrol on dextran sodium sulfate (DSS)-induced colitis in mice and found that it effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
179
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(196 citation statements)
references
References 41 publications
17
179
0
Order By: Relevance
“…Though most reports on the mechanism of RSV-induced biological effects focused on its allosteric effect on Sirt1 leading to increased enzymatic activity, RSV is also reported to increase the expression of Sirt1 through unknown mechanisms (42). It is possible that enhanced Sirt1 expression, along with increased activity, may further augment recovery or Sirt1 upregulation and this may be the primary mechanism of RSV-mediated salutary effect.…”
Section: Discussionmentioning
confidence: 99%
“…Though most reports on the mechanism of RSV-induced biological effects focused on its allosteric effect on Sirt1 leading to increased enzymatic activity, RSV is also reported to increase the expression of Sirt1 through unknown mechanisms (42). It is possible that enhanced Sirt1 expression, along with increased activity, may further augment recovery or Sirt1 upregulation and this may be the primary mechanism of RSV-mediated salutary effect.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with polyphenol has also been shown to prevent or delay the progression of IBD [40]. We have reported that orally administered resveratrol ameliorates both dextran sodium sulphate (DSS)-induced and IL-10 -/-chronic colitis in mice [41,42]. Our studies suggest that resveratrol targets multiple signaling pathways, including silent mating type information regulation-1 (SIRT1) gene expression, which has not been previously investigated with regard to its association with colitis.…”
mentioning
confidence: 77%
“…Our studies suggest that resveratrol targets multiple signaling pathways, including silent mating type information regulation-1 (SIRT1) gene expression, which has not been previously investigated with regard to its association with colitis. To this end, colitis induction may downregulate SIRT1 levels and promote both NF-kB activation and cytokine expression in the colon, and resveratrol reverses these effects by upregulating SIRT1 [41]. Furthermore, resveratrol treatment suppresses all indicators of inflammation including cytokine production and Th1 cell development as well as COX-2 expression and activation, thereby diminishing colitis.…”
mentioning
confidence: 99%
“…Till date, A substantial number of studies in cultured cells, animal models and human clinical trials have illustrated a protective role of dietary polyphenols against different types of cancers [17][18][19][20]. Polyphenols are present in fruits, vegetables, and other dietary botanicals.…”
Section: Dietary Polyphenols and Cancer Chemopreventionmentioning
confidence: 99%